Investigations on Entrepreneurship Needs, Challenges, and Models for Countries in Transition to Sustainable Development from Resource-Based Economy—Qatar as a Case - Mohammad I. Al-Housani (19170967) (2023)
This paper presents a comprehensive and comparative investigation into the needs, challenges, and potential roles for entrepreneurship in transforming resource-rich countries into sustainable economies. It explores the role of entrepreneurship to help transition from a resource-based economy, mainly through increasing the number of entrepreneurs and enhancing private-enterprise-led and small and medium enterprises to achieve economic diversification. This study focuses on the case of Qatar, considering its current policies, mechanisms, and institutes, and how they are working together to help diversify the economy and ultimately transition from its current resource-based economy. It begins with a comprehensive review of the literature, including a discussion of the significance of economic diversification globally and examining the role of government and other actors in developing entrepreneurship and the private sector. The methodology and conditions are set out, followed by the findings of the qualitative interview study with key and representative stakeholders within the existing entrepreneurship arena, such as entrepreneurs (successful or failed), those wanting to be entrepreneurs, policymakers, investors, and supporting agencies. The interviews are thematically analyzed to identify apparent challenges, their root causes, and initial recommendations. Three barriers in the entrepreneurship ecosystem in Qatar are identified: (1) lack of a conducive and transparent legal, regulatory, and governance environment, (2) lack of access to risk-based financing for entrepreneurs, and (3) lack of locally relevant entrepreneurial mentorship and guidance. Finally, the authors used the literature review and interview results to develop a progressive, locally tailored, dynamic preliminary framework for Qatar, and similar countries, to increase the number of entrepreneurs and small businesses to achieve economic growth and diversification. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su15097537